2006
DOI: 10.1111/j.1460-9568.2006.05050.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and structural brain deficits: a volumetric MR investigation

Abstract: Growing evidence from animal studies indicates brain-damaging properties of nicotine exposure. Investigations in humans found a wide range of functional cerebral effects of nicotine and cigarette smoking, but studies focusing on brain damage are sparse. In 22 smokers and 23 never-smokers possible differences of the cerebral structures were investigated using magnetic resonance imaging and voxel-based morphometry. Significantly smaller grey matter volume and lower grey matter density (P = 0.05, corrected) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
260
8
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(304 citation statements)
references
References 85 publications
34
260
8
2
Order By: Relevance
“…Consistent with the above literature, studies suggest chronic cigarette use is also associated with altered structure [24][25][26] and function [13,27] of the prefrontal cortex.…”
Section: Journal Of Addiction Research and Therapysupporting
confidence: 70%
“…Consistent with the above literature, studies suggest chronic cigarette use is also associated with altered structure [24][25][26] and function [13,27] of the prefrontal cortex.…”
Section: Journal Of Addiction Research and Therapysupporting
confidence: 70%
“…*P < 0.05, **P < 0.01 cortical thickness of the raINS and found a negative association with pack-years, cigarette dependence and urge to smoke (Morales et al 2014). Other studies have found lower GM density in the insula in smokers (compared with non-smokers) (Gallinat et al 2006;Fritz et al 2014), perhaps demonstrating the effect of nicotine and other constituents of tobacco smoke on this brain structure. Similarly, anticipation of nicotine administration (Gloria et al 2009) and administration itself (Stein et al 1998;Kobiella et al 2014) have been found to activate the aINS across fMRI studies, indicating that nicotine intake from smoking may affect insula activity as well.…”
Section: Discussionmentioning
confidence: 87%
“…[67][68][69][70][71] As commonly observed, the percentage of smokers was higher in patients than controls, 72 and smoking has been shown to have effects on cortical structure. [73][74][75][76][77] Although our results were maintained when controlling for smoking status, it cannot be excluded that smoking could have had an impact on the outcome. Also, controlling for medication use in our crosssectional study design might have disguised disease effects, and the observed medication effects might have influenced nontrivial interactions between morphology and different medication types.…”
Section: Limitationsmentioning
confidence: 99%